Morphometric analysis of the skulls of a ram and ewe Romanov sheep (Ovis aries) with 3D modelling - Barış Can Güzel; Fatma İşbilir (Veterinary Medicine and Science, 2024)
Abstract Background With the development of technology, 2D images have left their place for 3D models. The 3D modelling technique is widely used in plastic surgery, orthopaedic surgery, neurosurgery, traumatology, dentistry and medical education. The skull is important in terms of containing the starting parts of systems with vital functions. Objective The aim of the study is to reveal the difference between male and female and other species by 3D (three‐dimensional) modelling and craniometric measurements of Romanov heads. Methods In our study, skulls of Romanov sheep (10 females and 10 males) older than 1‐year‐old were used. The heads of Romanov sheep were scanned with computed tomography and modelled in 3D. Results and Conclusions In the study, it was determined that there was a statistically significant difference between male and female sheep in terms of the largest nose length, facial width, molar row length, viscerocranium length, and foramen magnum height parameters (p < 0.05). It was determined that the greatest width of the foramen magnum measurement parameter and the skull index showed statistically significant differences between the genders at the p < 0.01 level. No statistically significant difference was found in other measurements (p > 0.05). The data obtained as a result of the study will help in the racial discrimination and classification of bones obtained from zoo archaeological excavations.